Interaction of Bradykinin and B2 Bradykinin Receptor Antagonists with Colloidal Au Surface Explored by Surface-Enhanced Raman Scattering - Dominika Skołuba; Dariusz Sobolewski; Adam Prahl; Edyta Proniewicz (Journal of Spectroscopy)
Bradykinin (BK), an endogenous peptide hormone, which is involved in a number of physiological and pathophysiological processes, and the potent B2 bradykinin receptor antagonists, [D-Arg0,Hyp3,Thi5,8,L-Pip7]BK, Aaa[D-Arg0,Hyp3,Thi5,8,L-Pip7]BK, [D-Arg0,Hyp3,Thi5,D-Phe7,L-Pip8]BK, and Aaa[D-Arg0,Hyp3,Thi5,D-Phe7,L-Pip8]BK, were deposited onto colloidal Au particles of 20 nm size. Interaction of these molecules with colloidal Au surface was explored by surface-enhanced Raman scattering (SERS). Briefly, it was shown that BK adsorbs on the Au surface mainly through the Phe5/Phe8 residues. In case of the BK specifically modified analogues mainly the Pip and Thi rings are involved in the interaction process; however, Pip and Thi adopt slightly different orientation with respect to Au for each of the analogues. In addition, the lack of the Aaa vibrations, together with the enhancement of the Thi, Pip, or Phe modes, emphasizes the importance of the C-terminus in the interaction with the Au surface.